(untitled) (Medico Legal Update, 2021)
This study aims at the possibility of using the sk gene encoding the Streptokinase protein to differentiate between the different species belonging to the genus Streptococcus which can produce this protein., 12 bacterial isolates belonging to the genus Streptococcus were obtained, and by using thecaseinolytic assay test, all the studied isolates gave a positive result with different clear zone diameters around the wells. DNA was then extracted from the isolated bacteria and used as a template for the amplification of the sk gene using specific primers for the gene. The 1300 bp was amplified as PCR product comparing them with the DNA ladder. The target gene was obtained from of S. pyogenes and S. dysgalactiae subsp. equisimilis. . The result was confirmed by identifying the gene sequences and comparing it with the database in NCBI, which showed a similarity of more than 98% and the percentage of similarity between the genes of the different species was more than 99%. The sk gene for both species were digested with BtgZI and MboII restriction enzymes. The results of the agarose gel electrophoresis showed that the gene belonging to the S. pyogenes possesses restriction sites for BtgZI restriction enzymes that differ in location from that of the S. dysgalactiae subsp. equisimilis. Where the bundles appeared in different locations, which means that the location and number of restriction sites differ between the two types, and this feature can be used to differentiate between them.